2014
DOI: 10.1080/02640414.2013.861605
|View full text |Cite
|
Sign up to set email alerts
|

Physiological, movement and technical demands of centre-wicket Battlezone, traditional net-based training and one-day cricket matches: a comparative study of sub-elite cricket players

Abstract: This study compared physiological, physical and technical demands of Battlezone, traditional cricket training and one-day matches. Data were initially collected from 11 amateur, male cricket players (age: 22.2 ± 3.3 year, height: 1.82 ± 0.06 m body mass: 80.4 ± 9.8 kg) during four Battlezone and four traditional cricket training sessions encompassing different playing positions. Heart rate, blood lactate concentration, rating of perceived exertion and movement patterns of players were measured. Retrospective v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
60
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(64 citation statements)
references
References 20 publications
4
60
0
Order By: Relevance
“…These results concur with previous data that has observed game-based training to provide a more matchspecific physical demand, particularly in regards to high-intensity performance for spin bowlers (21,22). The more closely matched loads resulting from centre-wicket practice is likely the result of the greater proportion of distance spent performing at a high-intensity, and less time between low-and high-intensity efforts.…”
Section: Spin Bowlerssupporting
confidence: 83%
“…These results concur with previous data that has observed game-based training to provide a more matchspecific physical demand, particularly in regards to high-intensity performance for spin bowlers (21,22). The more closely matched loads resulting from centre-wicket practice is likely the result of the greater proportion of distance spent performing at a high-intensity, and less time between low-and high-intensity efforts.…”
Section: Spin Bowlerssupporting
confidence: 83%
“…Reported HR across each of these approaches, as well as the simulated 7-over bout developed by Christie et al 3 have been shown to vary across studies (BATEX: 130-144 beats•min -1 ; The Battlezone: 164 ± 12 beats•min -1 ; 7-over bout: 145 ± 11 beats•min -1 ). 3,5,6, 28,32,33 Furthermore, HR during BATEX and 7-over bout increased with protocol progression, reaching 147-159 beats•min -1 by the final stage/over. 3,5,6,32 Subsequently, these simulated protocols appear to invoke comparable or greater HR than those evident during Twenty20 and One-Day game-play.…”
Section: Internal Responsesmentioning
confidence: 92%
“…Researchers have provided HR measurements for batsmen across actual games, simulated play, and training scenarios. Specifically, mean absolute HR of 149 ± 17 beats•min -1 have been observed during Twenty20 games in second-tier international batsmen, 8 while responses of 144 ± 13 beats•min -1 and 159 ± 12 beats•min -1 were reported in second-tier international 8 and first team club batsmen 28 during One-Day games, respectively. The reported HR data also demonstrate some important time-course responses with spikes in HR showing players reach 97% of HRmax and spend considerable proportions of batting time (63%) working above an intensity of 75% HRmax.…”
Section: Internal Responsesmentioning
confidence: 93%
See 2 more Smart Citations